Effects of Winding Vibration on the Mechanical-Thermal Aging Properties of Insulating Paper - Junhong Wang; Ruijin Liao; Li Cheng; Zhidong Cheng (IEEE Access, 2020)
The oil-paper insulation in power transformer is under a complicated environment, and there is little research on the combined effects of winding vibration-generated mechanical stress and thermal stress on the aging of insulating paper. To investigate the effects of combined mechanical-thermal stress on the aging properties of insulating paper, this paper carried out accelerated aging test using the as-designed mechanical-thermal stress combined aging oven in the aging environment at the temperature of 130 °C, and the mechanical stress intensities of 1 MPa, 1.5 MPa and 2 MPa. Besides, the degree of polymerization (DP), tensile strength, infrared spectroscopy, and scanning electron microscope (SEM) tests were performed on the aging paper samples. The test results suggested that, the combined mechanical-thermal aging might be regarded as thermal aging with lower degradation activation energy; the DP and tensile strength of insulating paper markedly declined during the mechanical-thermal aging process. At the same time, mechanical stress promoted the destruction of glycosidic bond, intramolecular and intermolecular hydrogen bonds, and increased the insulating paper cracks and holes. Typically, the above factors accelerated the aging of insulating paper. Finally, an improved degradation rate equation for insulating paper with consideration of mechanical stress was put forward.